Learning process analysis based on industrial products in mechanical practices - Heri Yudiono (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
Revitalization of vocational education must be designed and developed according to the industry's needs through appropriate learning innovations. The selection of suitable learning methods influences the graduate competencies and learning experiences of students. This study aims to analyze the learning process based on industrial products in mechanical practices. The learning process analysis includes giving apperceptions and motivation, mastering learning materials, learning strategies implementation, learning resources or media, involving students, and closing the learning process. The research used an experimental method with a static group comparison design. This study used two groups consisting of the experimental and control group with 20 respondents for each. The experimental group is respondents who used industrial products-based learning, and the control group is respondents who used conventional learning (job sheet-based). The research respondents were students of the Mechanical Engineering Department Universitas Negeri Semarang who have passed the Mechanical Process I lesson chosen by random sampling technique. Research data were collected using a teaching and learning process questionnaire, while the data analysis technique used is the Mann Whitney U Test and descriptive statistics. The research findings show that there are differences in the process of the mechanical practice using industrial products-based learning and conventional learning (job sheet-based). Implementation of learning with the gift of apperception and motivation, mastery of learning materials, application of learning strategies, assembling of learning resources or learning media, students' participation in the learning process, and closing the learning process is better to use the industrial products-based learning compared to conventional learning.